Analysis of antioxidants in Chrysanthemum indici flos by online gradient extraction and HPLC-FRAP. Issue 20 (10th May 2021) - Fan, Weifeng; Zhou, Jianqiao; Wu, Zi; Tan, Guoying; Li, Haoxiang; Mei, Quanxi; Qian, Zhengming
Abstract : Analysis of antioxidants in Chrysanthemum indici flos by online gradient extraction and HPLC-FRAP. Abstract : Chrysanthemum indici flos (CIF), a traditional functional beverage, has been used in China for thousands of years. However, research on the antioxidant properties and compounds in CIF is insufficient. In the current study, an online gradient extraction (OGE) coupled with a high performance liquid chromatography-ferric reducing antioxidant power (HPLC-FRAP) system for rapid identification of antioxidants in CIF was proposed. The CIF sample (0.3 mg) was extracted online by a gradient mobile phase (acetonitrile and 0.1% formic acid), separated on a Poroshell 120 SB-Aq column, and then detected for the anti-oxidative activity with the online FRAP assay. 36 peaks were found and 28 compounds were identified. Among them, 18 peaks showed antioxidant activity, six of which were detected in CIF for the first time. The total analytical time was less than 45 min, including sample extraction, separation, and antioxidant identification. The results indicate that the OGE-HPLC-FRAP system is a simple, efficient and rapid tool for screening antioxidants in CIF, which provides the scientific data of CIF's antioxidant research and is helpful to improve the quality evaluation of CIF.